2018
DOI: 10.1097/scs.0000000000004376
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing and Temporomandibular Disorders in Adults

Abstract: Nonhealthy patients presented a time of swallow higher than HP (P < 0.001). Nonhealthy patients presented a higher muscles activation and time of swallow than HP and a decrease of muscles balancing activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Among the individuals with TMD in the present study, 81% presented atypical swallowing biodynamics in the pharyngeal phase. A similar finding (70% of the sample) has been reported in patients with severe TMD (Maffei et al, 2012) and this result is in agreement with observational studies of the oral phase of swallowing (Ciavarella et al, 2018;Ferreira et al, 2009;Ferreira et al, 2019;Marim et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Among the individuals with TMD in the present study, 81% presented atypical swallowing biodynamics in the pharyngeal phase. A similar finding (70% of the sample) has been reported in patients with severe TMD (Maffei et al, 2012) and this result is in agreement with observational studies of the oral phase of swallowing (Ciavarella et al, 2018;Ferreira et al, 2009;Ferreira et al, 2019;Marim et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…Swallowing is one of the most commonly altered orofacial functions in individuals with TMD (Ciavarella et al, 2018;Fassicollo et al, 2019;Ferreira et al, 2009;Ferreira et al, 2019;Gilheaney et al, 2017;Marim et al, 2019). In an observational study of the oral phase of swallowing, abnormalities were found in 78.75% of individuals with TMD (Ferreira et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well‐known that teeth contact, jaw control, tongue position, hyoid bone position and temporomandibular joint stability are very important during swallowing, which is one of the most important oral functions. A recent study showed that TMD patients presented higher masseter and temporalis activation and an unbalancing of temporalis and submental muscle activation during saliva swallowing than healthy controls; this may be correlated to a modification of tongue position in the mouth. In clinical practice, a small proportion of TMD patients complain of swallowing dysfunction.…”
Section: Discussionmentioning
confidence: 97%
“…9 Many authors link the occurrence of parafunctions with the signs and symptoms of TMD. 2,6,11,12 In turn patients who suffer from TMD also have increased levels of cortisol and the coexistence of other negative emotional states such as depression or somatization of symptoms. 13 Considering that stress is a risk factor in para-functional habits and TMD, high levels of cortisol can combine these two disorders.…”
Section: Introductionmentioning
confidence: 99%